Ulcerous Colitis in Mexico: Is It Still a Diagnostic-Therapeutic Myth? 20 Years of Experience - Sánchez, Morelos Adolfo García; González, Mireya Fuente; Cortés, Imelda Yasmín Palma; Rodríguez, María Isabel Estrada; Estrella, Mara Luz Terán; Godínez, Jennifer Itzel Jacobo; Longines, Fabian Cazares; García, Giselle Castillo; Jiménez, Alejandro Altamirano; Vargas, Astrid Ortiz; García, Baruj Ricardo Lupio; Barrón, Gema Méndez; et al. (British Journal of Healthcare and Medical Research, 2023)
Nonspecific chronic ulcerative colitis is a variety of inflammatory bowel diseases which to date is of unknown etiology. The objective is to present the experience of 20 years in the diagnosis and treatment, in a multicenter study of nonspecific chronic ulcerative colitis in Mexico. With a study methodology with a retrospective, longitudinal, observational and descriptive design, in the Colon and Rectal Surgery and General Surgery services. Results: 181 patients with histopathologically confirmed diagnosis: 76 women (42%) and 105 men (58%). With an age range of 16 to 85 years, with a mean of 39 years, with a follow-up of 1 to 5 years from diagnosis, both clinically and colonoscopically; 63 cases (36) required surgery, 10 patients with colorectal cancer (2%): severe dysplasia and/or tumor (neoplasia), anal surgery reaches up to 25%. The statistical or epidemiological data of non-specific chronic ulcerative colitis to date are unknown or not very relevant to the public or private Health System in Mexico and/or in most of the world, with unreliable information, without scientific validation and only by the experience of some physicians with little unpublished casuistry.